Analisis Iklan Jaminan Saldo Kembali dari Gopay Dalam Perpektif Teori Design Thinking - Pahlevi, Syah Reckha (CITRAWIRA : Journal of Advertising and Visual Communication, 2022)
Improvement of technology is opening an oppurtunity for advertising to display the advertisement in many media. Now the company faces many form of media that can be used as advertising media. One of the media with a positive feedback for advertising media is streaming platform, for exempelr there is Youtube. Recently, GoPay as digital wallet service from GoJek company published an advertisment that have different look, it use two dimension animation format. Rubber Hose is the stlye that represent the style of animation in year 1930s used for the GoPay advertisement this time. This paper will be critisize and analyze based on design thinking theory by Tim Brown that consist of three phase, there are inspiration, ideation, and implementation about an advertisment that tittled “Jaminan Saldo Kembali dari Gopay”.